Pedological characterization and soil fertility assessment of the selected rice irrigation schemes, Tanzania - Marzouk, Said H.; Tindwa, Hamis J.; Massawe, Boniface H. J.; Amuri, Nyambilila A.; Semoka, Johnson M. (Frontiers in Soil Science, 2023)
Rice (Oryza sativa L.) is the second cereal food crop grown in Tanzania after maize (Zea mays L.) and covers approximately 18% of the agricultural land. Soil degradation due to intensive cultivation along with low organic matter input and nutrient imbalance has led to a decline in rice crop yields. This study was conducted to characterize, classify, and assess the fertility status of soils in two rice irrigation schemes of Morogoro region in Tanzania. The data obtained through this study will contribute significantly to land use planning and will facilitate the transfer of agro-technology and other development of the regions with similar ecological conditions. The studied pedons were named MKU-P1 and MKD-P1 for Mkula and Mkindo irrigation schemes, respectively. A total of seven composite soil samples (0–20 cm) were collected for soil fertility assessments. Landform, soil morphological features, parent material, natural vegetation, drainage, erosion, and laboratory data were used to classify the soils in their respective order as per the United States Department of Agriculture (USDA) Soil Taxonomy and the World Reference Base (WRB) soil classification systems. Results showed that the pedons were sandy clay loam in the topsoil and sandy clay to clay in the subsoil; soil reaction ranged from medium acid (pH 5.7) to strongly alkaline (pH 8.6). The topsoil and subsoil nutrients of the studied pedons including available K+, total N, soil organic matter, and organic carbon are low. Based on the USDA Soil Taxonomy, MKU-P1 is classified as Inceptisols cumulic humaquepts and MKD-P1 as Vertisols Fluvaquentic endoaquerts corresponding to Subaquatic fluvisols (loamic, oxyaquic) and Irragric vertisols (gleyic) in the WRB, respectively. The pedons were ranked as suitable for rice production. However, the chemical fertility of the soil is ranked as low fertile associated with deficient in total N; available P, K+, and Ca2+ with excessive iron and manganese; and likely to pose toxicity to crops. The application of organic and mineral amendments in recommended rates and timing for N and P is therefore essential to increase the nutrient content of these soils and minimize losses. Salinity in the subsurface pedon MKD-P1 needs to be taken into future consideration.